A relation between serum albumin level and prognosis of critically ill children admitted to the pediatric ICU - Gowa, Murtaza Ali; Tauseef, Usman; Ahmed, Syed Habib (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the frequency of hypoalbuminemia in critically ill children, and to assess the association of low serum albumin with clinical deterioration and outcome. Method: The prospective, descriptive study was conducted from September 1, 2020, to October 31, 2021, at the National Institute of Child Health, Karachi, and comprised critically ill children of either gender aged between 3 months and 16 years admitted to the paediatric intensive care unit. Serum albumin values were documented at 2 hours post-admission and at 24 hours. Paediatric Index of Mortality 2 score, Vasoactive Inotropic Score, and Paediatric Sequential Organ Failure Assessment scores were calculated. Hypoalbuminemia was defined as serum albumin 3.3gdl. Data was analysed using SPSS 27. Results: Of the 110 patients, 70(63.6%) were boys and 40(36.4%) were girls. The overall mean age was 46.72±43.28 months. Hypoalbuminemia at 24 hours was found in 74(67.3%) subjects compared to 60(54.5%) at 2 hours, and mean serum albumin was lower at 24 hours compared to 2 hours post-admission (p<0.05). Patients with hypoalbuminemia had significant relation with Paediatric Index of Mortality 2 score, Vasoactive Inotropic Score, Paediatric Sequential Organ Failure Assessment score, and outcome (p<0.05). The risk of mortality was 4.1 times higher in patients with hypoalbuminemia (p=0.001). Conclusion: The incidence of hypoalbuminemia was found to be higher in children in intensive care settings, and hypoalbuminemia was a significant independent predictor of mortality in a critically ill child. Key Words: Hypoalbuminemia, Serum albumin, Critically ill, Children, PICU, Prognosis.